PENGARUH PROFITABILITAS, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN RESIKO BISNIS TERHADAP STRUKTUR MODAL - Nanda, Desty Widya; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to test the influence of profitability, managerial ownership, institutionalownership, and business risk to the capital structure through annual financial statement which has beenprepared by Food and Beverages companies which are listed in Indonesia Stock Exchange in 2013-2015 periods.The samples of this research has been obtained by using purposive sampling method and based on thepredetermined criteria, 12 companies with the numbers of observation are 36 companies have been obtained assamples. The analysis method has been carried out by using multiple linear regressions analysis. Based on theresult of the test, it can be concluded that: (1) profitability has negative influence to the capital structure. Itoccurs because when the company has high profitability, the company tends to have relatively low debt and whenthe profitability is high it has large amount of fund and retain earning so that companies tend to use their retainearning instead of debt; (2) Managerial ownership does not have any influence to the capital structure. It occursbecause of the stock ownership by the manager is low; (3) Institutional ownership does not have any influence tothe capital structure. It occurs because of the commissioner and institutional policies of a company has beenlimited by managerial policies as the corporate management mechanisms so the policies which are related to thecapital structure cannot be decided by the institutional itself; (4) Business risk has positive influence to thecapital structure. It occurs because when the business risk of a company is getting high, the debt ratio is gettinghigh as well.Keywords: Profitability, managerial ownership, institutional ownership, business risk, capitalstructure.